Symbolic representation in Kant's practical philosophy - Bielefeldt, Heiner, 1958- (Cambridge University Press, 2003)
This book explores in detail the role that symbolic representation plays in the architecture of Kant's philosophy. By showing how the nature of symbolic representation plays out across all areas of Kant's practical philosophy Heiner Bielefeldt offers a unique perspective on how these various facets of Kant's philosophy cohere.